Scientific writing: kKnowledge of nursing students (Research, Society and Development, 2021)
Cognition is something intrinsic to human beings, and it unfolds through a chain of stages that disagree with the type of learning, which can be related to religion, philosophy, popular and artistic. The process of reading and writing are activities present in the academic experience, through which the knowledge of the practices of the university's future career originates. The objective is to assess the level of understanding of students to deal with scientific writing. This is a descriptive research, with a quantitative approach, carried out in a higher education institution in the state of Sergipe. Data analysis was performed using the Statistical Package for Social Sciences for Windows - SPSS version 21 and Microsoft Excel 2010 and distributed in absolute and relative frequencies. It was found that only 7.05% of respondents, out of a total of 170 academics, had knowledge about scientific writing. Finally, the offer of the online discipline and the role of teachers in the development of scientific-critical knowledge of students are discussed.